Conversational Implicature in Tim Burton’s Netflix Series “Wednesday” - Fadillah Ayu Natasya; Sukardi Weda; Murni Mahmud (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This study examines the use of conversational implicature in the Netflix series by Tim Burton, "Wednesday." The aim of this research is to identify and interpret the types of conversational implicature used by the characters. A descriptive qualitative method was employed to collect data, which involved watching all eight episodes of the series and transcribing selected utterances. The data was then analyzed and interpreted according to Grice's theory and Levinson’s theory of conversational implicature, focusing on both generalized and particularized types of conversational implicature. The findings show that particularized conversational implicature is used more frequently by the characters in this series, with 25 instances, compared to 5 instances of general conversational implicature. The maxim of quantity was the most commonly flouted, followed by the maxims of manner, relevance, and quality. The findings of this study clarify cases in previous research where specific conversational implicature was mistakenly classified as general conversational implicature. This study contributes to the field of pragmatics and provides valuable insights for the academic community, particularly for teachers, students, and further research, in understanding the types of conversational implicatures and the implicit meaning behind an utterance.Keywords: Conversational Implicature, Wednesday, Generalized Implicature, Particularized Implicature